Populations potentially exposed to traffic-related air pollution in seven world cities. (May 2015) - Su, Jason G.; Apte, Joshua S.; Lipsitt, Jonah; Garcia-Gonzales, Diane A.; Beckerman, Bernardo S.; de Nazelle, Audrey; Texcalac-Sangrador, José Luis; Jerrett, Michael
Abstract: Traffic-related air pollution (TRAP) likely exerts a large burden of disease globally, and in many places, traffic is increasing dramatically. The impact, however, of urban form on the portion of population potentially exposed to TRAP remains poorly understood. In this study, we estimate portions of population potentially exposed to TRAP across seven global cities of various urban forms. Data on population distributions and road networks were collected from the best available sources in each city and from remote sensing analysis. Using spatial mapping techniques, we first overlaid road buffers onto population data to estimate the portions of population potentially exposed for four plausible impact zones. Based on a most likely scenario with impacts from highways up to 300 meters and major roadways up to 50 meters, we identified that the portions of population potentially exposed for the seven cities ranged from 23 to 96%. High-income North American cities had the lowest potential exposure portions, while those in Europe had the highest. Second, we adjusted exposure zone concentration levels based on a literature suggested multiplier for each city using corresponding background concentrations. Though Beijing and Mexico City did not have the highest portion of population exposure, those in their exposure zones had the highest levels of exposure. For all seven cities, the portion of population potentially exposed was positively correlated with roadway density and, to a lesser extent, with population density. These analyses suggest that urban form may influence the portion of population exposed to TRAP and vehicle emissions and other factors may influence the exposure levels. Greater understanding of urban form and other factors influencing potential exposure to TRAP may help inform interventions that protect public health. Graphical abstract: Highlights: Potential population exposure to traffic-related air pollution across seven global cities Relationships between population exposure and roadway/population density Remote sensing data for refining the spatial distribution of population Exposure levels for those people living in the most likely exposure zone Suggestions that may help inform interventions that protect public health